Chest wall reconstruction in benign and malignant tumors with non-rigid materials: An overview - Colella, Sara; Brandimarte, Alessandro; Marra, Roberta; Marinari, Stefano; D’Incecco, Armida; Di Genesio Pagliuca, Milena; De Vico, Andrea; Crisci, Roberto; Divisi, Duilio (Frontiers in Surgery, 2022)
Several materials and techniques have been described for the procedure of chest wall reconstruction: the choice of using a technique or a material over another one relies mainly on surgeon’s experience as well as thoracic defect localization and dimension, local availability of materials, and costs. From a technical point of view, autologous or alloplastic reconstruction are available and, in both cases, rigid and non-rigid protheses are found. Each material has its own peculiarities, with advantages and disadvantages, thus it is mandatory to be confident when planning the intervention in order to foresee possible complications and minimize them. We have systematically reviewed literature about chest wall reconstruction in chest wall tumors (both malignant and non-malignant) with non-rigid prosthetic materials, focusing on safety outcomes.